Penegakan Hukum Pencucian Uang di Sektor Perbankan - Eti Mul Erowati; Prosawita Ririh Kusumasari (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
Money laundering in the Indonesian banking sector has become a major issue affecting economic stability and national security. This article analyzes the implementation of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering, focusing on the challenges in identifying and handling illegal transactions amidst the complexity of the financial system. Through a qualitative method with a normative legal approach, this study reveals various weaknesses in the implementation of existing regulations. The results of the study indicate the need to update the legal framework to be more responsive and effective in dealing with the dynamics of money laundering. Recommendations put forward include strengthening cross-agency cooperation, utilizing advanced technology to detect suspicious transactions, and increasing education and training for stakeholders in the banking sector. This strategy is expected to not only strengthen domestic supervision but also encourage international collaboration to combat money laundering more broadly. The findings of this study emphasize the importance of adaptive regulatory updates and the use of technological innovation to create a more transparent and secure financial system. With these steps, it is hoped that Indonesia will be able to strengthen economic stability, increase public trust in the banking sector, and contribute to global efforts to eradicate financial crime.